(untitled) (diségno, 2022)
Within its premises, the MAXXI (National Museum of 21st Century Arts) of Rome houses the first Italian museum of architecture. Conceived since its genesis as a place of synthesis capable of activating a reciprocal and uninterrupted dynamic between research, documentation, conservation, production and exhibition, MAXXI started its activities in 2010 reflecting on the archive/museum model experimented in various international institutions. The binomial archive/museum –a binomial that always alludes to coordinated and to a certain extent overlapping functions (conserving, consulting, exhibiting, promoting, disseminating)– has characterized the cultural project of the Museum of architecture since its inception, defining its physiognomy and identity. [read more]